Creep damage evolution process of asphalt binder based on viscoelastic characteristics - Xiaofei Qi; Shuang Tian; Liyan Shan; Shuang Liu; Yajie Wang (Journal of Traffic and Transportation Engineering (English ed. Online), 2024)
The creep damage evolution of asphalt binder plays a significant role in investigating the formation mechanism of rutting. The rutting is the common distress at high temperatures for asphalt pavements. However, the reliability of existing creep damage parameters is under questioned, and these parameters cannot accurately illustrate the change of intrinsic microstructure for asphalt binder. In this paper, a new test protocol was given access to study the evolution of viscoelastic parameters during creep damage. It was completed by inserting the frequency sweep during creep test. The frequency sweep curve clusters were fitted by the generalized Kelvin-Voigt model for obtaining the change law of model parameters. Based on the change law and sensitivity analysis of model parameters, (E2 + E3)/2 was proposed as the creep damage variable. According to the curve of (E2 + E3)/2 versus loading time, two stages during the creep test could be identified: an approximate constant value in phase Ⅰ and a linear decrease in phase Ⅱ. Intrinsic differences about creep property of binders could be determined by this new proposed parameter. Above results not only ensure better understanding of the creep damage mechanism of binders, but also lay the theoretical foundation on predicting the anti-rutting performance of binders.